RADON CONCENTRATION MEASUREMENTS FOR DETERMINATION OF RADIATION DOSE AND ASSESSMENT OF CANCER RISK IN THE PREMISES OF SOME COLLEGES IN LAHORE, PAKISTAN - Iqbal, M. A.; Tufail, M.; Mahmood, A. (The Nucleus, 2010)
Radon concentration has been measured in campus and hostel buildings of some colleges in the city of Lahore. The technique of passive radon measurements was employed using CN−85 etched track detectors in the box type dosimeters. The observed radon concentration in different parts of monitored buildings was within the range 18−61 Bq m−3 . The cause of radon in college buildings may be the construction materials, drinking water, natural gas, drainage, sewerage pipes, etc. Moving fans, open doors and windows in summer season diluted the radon concentration, while the air tight arrangement in the winter enhanced the radon concentration level. Alpha dose from radon to the students and supporting staff was estimated as 0.34 and 0.91 mSv y−1 in campus and hostel buildings respectively. The corresponding excess lifetime cancer risk attributed to the students and staff in the college campuses was found to be 0.20 %, while the staff and students residing in the hostels of the colleges received the excess lifetime risk of cancer 0.53 % due to radon progenies.